2007
DOI: 10.1631/jzus.2007.b0715
|View full text |Cite
|
Sign up to set email alerts
|

Lance-adams syndrome: a report of two cases

Abstract: Chronic post-hypoxic myoclonus, also known as Lance-Adams syndrome (LAS), is a rare complication of successful cardiopulmanry resuscitation often accompanied by action myoclonus and cerebellar ataxia. It is seen in patients who have undergone a cardiorespiratory arrest, regained consciousness afterwards, and then developed myoclonus days or weeks after the event. Worldwide, 122 cases have been reported in the literature so far, including 1 case of Chinese. Here we report 2 Chinese LAS patients with detailed ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 18 publications
1
36
2
4
Order By: Relevance
“…A nonenhanced CT scan can also provide information about structural lesions, stroke, or intracranial hemorrhage that may have contributed to cardiac arrest. 268,269 Other less utilized and investigated neuroimaging modalities have included single-photon emission computed tomography, 253,267,270 cerebral angiography 244 and transcranial Doppler 240 A nuclear imaging study observed that abnormal tracer uptake in the cerebral cortices was associated with poor outcome in one case report. 248 Despite tremendous potential, neuroimaging has yet to be proved as an independently accurate modality for prediction of outcome in individual comatose survivors of cardiac arrest and specific neuroimaging modalities cannot be recommended for predicting poor outcome after cardiac arrest.…”
Section: Neuroimagingmentioning
confidence: 99%
“…A nonenhanced CT scan can also provide information about structural lesions, stroke, or intracranial hemorrhage that may have contributed to cardiac arrest. 268,269 Other less utilized and investigated neuroimaging modalities have included single-photon emission computed tomography, 253,267,270 cerebral angiography 244 and transcranial Doppler 240 A nuclear imaging study observed that abnormal tracer uptake in the cerebral cortices was associated with poor outcome in one case report. 248 Despite tremendous potential, neuroimaging has yet to be proved as an independently accurate modality for prediction of outcome in individual comatose survivors of cardiac arrest and specific neuroimaging modalities cannot be recommended for predicting poor outcome after cardiac arrest.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Cerebral neuroimaging studies are not useful for the diagnosis of Lance-Adams syndrome with the exception of brain single photon emission computed tomography (SPECT) and brain positron emission tomography (PET). Compared with control groups, patients with Lance-Adams syndrome have increased glucose metabolism in the pontine tegmentum, mesencephalon, and ventrolateral thalamus on PET (Frucht et al, 2004), and hypoperfusion in the temporal lobe on brain SPECT (Zhang et al, 2007). Further studies are needed to uncover reliable clinical and electrophysiological characteristics for the differentiation between myoclonus from severe hypoxic-ischemic encephalopathy and Lance-Adams syndrome.…”
Section: Cortical Myoclonus In the Icumentioning
confidence: 99%
“…There are no LOE P1-or LOE P2-studies that support the use of magnetic resonance imaging (MRI) to predict outcome of comatose cardiac arrest survivors. Use of MRI to predict outcome is supported by 32 studies (LOE P3 959 -963 ; LOE P4 964 -976 ; LOE P5 [977][978][979][980][981][982][983][984][985][986][987][988][989][990] ). The timing of MRI in these studies ranged from 1 day to 10 months after sustained ROSC.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Single photon emission CT (SPECT) is supported by 3 LOE P5-studies 990,1006,1009 and is opposed by 1 LOE P2-study. 1010 The timing of SPECT in these studies ranged from 1 to 23 days after sustained ROSC.…”
Section: Consensus On Sciencementioning
confidence: 99%